Role of Fentanyl With Bupivacaine During Spinal Anaesthesia for Caesarean Section in Reducing Hypotension - Mamun, Md Al; Alam, Md Rabiul; Akter, Suraya; Haque, Mozibul (Journal of the Bangladesh Society of Anaesthesiologists, 2019)
Background and Objectives: The hypotension following spinal anaesthesia is a common problem incaesarean section. The combination of reduced dose of local anaesthetics with intrathecal opioids makesit possible to achieve adequate spinal anaesthesia with minimum hypotension. We investigated whetherthis synergistic phenomenon could be used to provide less frequent hypotension while incurring adequatespinal anaesthesia for caesarean section. Methods: Sixty women scheduled for caesarean delivery (thirty in each group) were divided into twogroups of patients who received a spinal injection of either 12.5 mg of hyperbaric bupivacaine or 10 mgof hyperbaric bupivacaine with 25 mg fentanyl added. Each measurement of a systolic blood pressureless than 95 mmHg or a decrease in systolic pressure of greater than 25% from baseline was consideredas hypotension and treated with a bolus of 5 to 10 mg of intravenous ephedrine. The quality of surgicalanaesthesia was evaluated also. Results: Spinal block provided excellent surgical anaesthesia in almost all patients. Peak sensory levelwas higher (D2-3 vs. D4-5) and motor block was more intense in the hyperbaric bupivacaine group; thepatients from bupivacaine group were more likely to require treatment for hypotension (75% vs. 15%)and had more persistent hypotension (4.6 vs. 1.0 hypotensive measurements per patient) than patients inthe reduced bupivacaine-fentanyl group. Mean ephedrine requirements were 15.0 mg and 3.5 mg,respectively. Patients in the bupivacaine group also complained of emetic effects more frequently thanpatients in the reduced dose bupivacaine-fentanyl group. Conclusions: Bupivacaine 10 mg plus fentanyl 25 mg provided spinal anaesthesia for caesarean deliverywith less hypotension and vasopressor requirements while ensuring excellent perioperative surgical anaesthesia. JBSA 2019; 32(1): 28-34